A Nutrient Analysis Of Various Taro Varieties in The Sangihe Islands Region (International Forum of Researchers and Lecturers, 2024)
The Sangihe-Talaud region hosts several taro varieties whose nutritional compositions in raw, steamed, and fried states remain unknown. This study examined these varieties, their processing methods, and their impact on taro’s nutritional components, encompassing energy, protein, fat, carbohydrates, dietary fiber, ash, calcium, phosphorus, iron, vitamin C, moisture content, and sensory preferences. The investigation encompassed Macape Marramu, Macape Darrana, and Allae Mawira taro types subjected to raw, steamed, and fried treatments. In this study, the researchers employed a complete randomized design with two factors and four replications. The findings revealed diverse effects of treatments and their interactions on taro’s nutritional profile. Treatment A₁B₂ yielded the highest energy content at 116.6. The maximum protein content was observed in treatment A₂B₂. Treatment A₃B₂ exhibited the highest fat content at 6.87, whereas A₁B₁, while not significantly different from A₂B₁ and A₃B₁, showed lower fat content. Treatment A₂B₂ registered the highest carbohydrate content at 89.27. Treatment A₁B₂ resulted in the highest dietary fiber at 4.28. The lowest ash content was in treatment A₁B₁, while the highest was observed in treatment A₃B₂ at 1.07. Treatment A₃B₂ recorded the highest calcium at 125%. The maximum phosphorus content was noted in treatment A₃B₂, whereas the minimum was in A₂B₀. Treatment A₃B₂ exhibited the highest iron content. The richest vitamin C content emerged in treatment A₂B₂ at 15.79. The lowest moisture content was observed in treatment A₁B₂, which was not significantly different from A₂B₂ (Macape Darrana; fried). Meanwhile, the highest moisture content was observed in treatment A₂B₀.